Tat PTD–endostatin: A novel anti-angiogenesis protein with ocular barrier permeability via eye-drops - Zhang, Xinke; Li, Yan; Cheng, Yanna; Tan, Haining; Li, Zhiwei; Qu, Yi; Mu, Guoying; Wang, Fengshan (Biochimica et biophysica acta, 2015)
Endostatin, a specific inhibitor of endothelial cell proliferation and angiogenesis, has been proved to have effects on ocular neovascular diseases by intraocular injection. In order to increase its permeability to ocular barriers and make it effective on fundus oculi angiogenesis diseases via non-invasive administration (eye drops), endostatin was fused to Tat PTD via a genetic engineering method. Most of the Tat PTD– endostatin was expressed as inclusion bodies in Escherichia coli, so pure and active Tat PTD–endostatin was prepared by a series of operations, including inclusion body denaturation, refolding and chromatography. The anti-angiogenesis activity of Tat PTD–endostatin was investigated by cell proliferation experiments and chick embryo chorioallantoic membrane assay. In addition, its translocating ability and concrete entry mechanism into cells were also investigated by fluorescence microscope and flow cytometry. The penetrating ability to ocular barriers was also studied by immunohistochemistry. A mouse choroidal neovascularization model was established to investigate the pharmacodynamics of Tat PTD–endostatin. The obtained Tat PTD–endostatin had excellent anti-angiogenesis activity and was superior to Es in cellular translocating. Macropinocytosis may be the dominant route of entry of Tat PTD–endostatin into cells. Tat PTD–endostatin could cross ocular barriers and arrive at the retina after eye-drop administration. In addition, it displayed inhibitory effects on choroidal neovascularization via eye drops. Tat PTD–endostatin possessed excellent ocular penetrating ability and anti-angiogenesis effects. Tat PTD is a promising ocular delivery tool, and Tat PTD–endostatin is a potential drug for curing fundus oculi angiogenesis diseases. •Tat PTD–Es was obtained by bioengineering technology.•Tat PTD–Es performed excellent anti-angiogenesis activity.•Tat PTD–Es could cross ocular barriers after eye-drop administration.•Tat PTD is a promising ocular delivery tool.•Tat PTD–Es is a potential drug for curing fundus oculi angiogenesis diseases.